Coming to Terms Will Do It: Students Engaging With Climate Change Through Sensemaking and Collective Efficacy Perceptions - Sean Quartz (Central States Communication Association, 2022)
Within climate change instruction, effective instructional crisis communication is necessary to attain cognitive, affective, and behavioral learning outcomes so students comprehensively learn the reality and implications of this planetary crisis. I locate this learning as coming to terms with climate change. This study explores how students affectively and cognitively learned to come to terms with the immense threat of the climate crisis outside their initial exposure to climate change fear appeals communicated in their classrooms. Drawing from interviews and focus groups with college students, I found students came to terms with climate change outside their classrooms by coping with the immense threat while enacting sensemaking with their peers. These findings suggest coping and sensemaking are crucial for students to come to terms with climate change after instructor-delivered fear appeals to access the efficacy needed to face this planetary threat. Ultimately, this study advances instructional crisis communication by providing insight into student to student out-of-classroom communication and how it affects cognitive and affective learning outcomes concerning climate change.